(NiSTORIQ aRMENII mOISEQ hORENSKAGOs (NnOWYJ PEREWOD n(B. (No(B. (N|MINA S PRIME^ANIQMI I PRILOVENIQMIs - (NhORENSKIJ(B, (NmOISEJs; (N|MIN(B.(Nn(B. (No(B.s; (N|TNOGRAFI^ESKIJ fOND n(B.(No(B. (N|MINAs ((NmOSKWA (B:s (NtIPOGRAFIQ w(B. (Na(B. (NgATCUKs, 1893)
(NpOSMERTNOE IZDANIEs
(NpOSMERTNOE IZD(B.s
Keywords: (NaRMENIQs -- (NiSTORIQs